2011
DOI: 10.1111/j.1749-4486.2011.02292.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between acoustic rhinometry and visual analogue scale in children with no nasal symptoms: a prospective cohort study

Abstract: We conclude that VAS shows potential as a subjective tool to investigate nasal obstruction in children over 7 years of age. There was a correlation between VAS and acoustic rhinometry in children with no nasal symptoms at baseline. No correlation was found in children with decongested normal nasal airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Recently, Haavisto et al 21 reported that the VAS has potential as a tool to investigate subjective nasal obstruction in children (i.e. seven years and older), following their assessment of the correlation between VAS and acoustic rhinometry results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, Haavisto et al 21 reported that the VAS has potential as a tool to investigate subjective nasal obstruction in children (i.e. seven years and older), following their assessment of the correlation between VAS and acoustic rhinometry results.…”
Section: Discussionmentioning
confidence: 98%
“…Although VAS assessment of nasal obstruction has been validated against rhinomanometry only in adults, we elected to extrapolate such VAS assessment to children, as the VAS is a simple, readily available tool. Recently, Haavisto et al 21 . reported that the VAS has potential as a tool to investigate subjective nasal obstruction in children (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…To some extent, this was to be expected, as modest amounts of nonadherence may still leave patients within a ‘well-treated' therapeutic window [27]. Additionally, some studies have suggested there may be no correlation between the VAS estimates and objective parameters such as NAR, MCA, NCV, and nNO [28,29,30]. Nevertheless, about 95.0% of the patients in the SMS group indicated that they would like the SMS program to continue at the end of study, suggesting that a daily SMS reminder was related with the patients' perception of positive therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have argued that the MCA does not change significantly between the ages of 7 and 14 years 32,33 ; however, other studies have argued a strong correlation between age and MCA, as well as height and total body surface area with nasal volume. 17 This may have biased our results because what is considered a "normal" MCA may be different for each patient in the study. Establishing "normal" AR values according to patient height, age, and race/ethnicity has been difficult, with studies reporting conflicting ranges.…”
Section: Discussionmentioning
confidence: 96%